Utilizing Social Media Marketing to Influence Customer Purchase Intention and Trust in Influencers Who Also Act as Skincare Product Owners - Santoso, Ridho Bagus; Nurmitananda, Muhammad Naufal Hamdani; Premananto, Gancar Candra; Primasatya, Rieswandha Dio (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The skincare business presents a lucrative opportunity for revenue generation at both macro and micro levels. Influencers, with their large followings and social influence, have effectively leveraged this opportunity to establish skincare brands. This research aims to complement existing studies by examining how social media marketing conducted by influencers can impact consumer purchasing interest. The second objective is to propose effective marketing strategies via social media to enhance customer trust. Utilizing qualitative methods, the study applies netnographic data collection and literature reviews. The findings indicate that not all influencers with skincare businesses succeed in the competitive landscape of social media marketing. Influencers must develop strategic marketing plans, particularly focusing on the number of followers and engagement rates to build customer trust. Influencers with a unique appeal, such as celebrities, can be effective in boosting consumer interest in skincare products. This research emphasizes the importance of influencer selection and social media strategy in sustaining a skincare business.